2001
DOI: 10.1080/01448765.2001.9754906
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Plants for Protecting Stored Pulses fromCallosobruchus maculatus(Coleoptera: Bruchidae) Infestation

Abstract: The potential of 30 plant leaf or tuber extracts to protect pulses from attack by Callosobruchus mnculatus during post harvest storage was evaluated. Pulses were stored in gunny bags treated with I 0% aqueous plant extract and kept in individual containers harbouring newly emerged adult C. mnculatus. Mean number of eggs laid, adult emergence and seed weight loss were recorded. From the laboratory studies, ten plants were identified as effective in protecting pulses. Effective plants were tested in farmers fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…The reduction in the number of F 1 progeny produced by C. maculatus suggests the presence of ovicidal properties in the seeds of C. colocynthis and it could be as a result of eggs of C. maculatus were brought in closer contact with toxic secondary metabolites in C. colocynthis thus causing higher egg mortality that inhibited adult emergence so greatly in treated seeds than control seeds. Other studies have shown that botanicals inhibited F 1 progeny production and adult emergence of C. maculatus in cowpea [13,[29][30][31][32]. These studies further suggested that when eggs are laid on treated seeds, the toxic substance present in the extract may enter into the egg through chorion and suppressed further embryonic development, which are in general agreement with our present findings.…”
Section: Discussionsupporting
confidence: 83%
“…The reduction in the number of F 1 progeny produced by C. maculatus suggests the presence of ovicidal properties in the seeds of C. colocynthis and it could be as a result of eggs of C. maculatus were brought in closer contact with toxic secondary metabolites in C. colocynthis thus causing higher egg mortality that inhibited adult emergence so greatly in treated seeds than control seeds. Other studies have shown that botanicals inhibited F 1 progeny production and adult emergence of C. maculatus in cowpea [13,[29][30][31][32]. These studies further suggested that when eggs are laid on treated seeds, the toxic substance present in the extract may enter into the egg through chorion and suppressed further embryonic development, which are in general agreement with our present findings.…”
Section: Discussionsupporting
confidence: 83%
“…The use of essential oils had equally been adopted and proven effective. Raja et al, (2001) reported that pulse stored in gunny bags and treated with aqueous extracts from leaves of Melia azadirachta, Hyptis suaveolens and tuber of Cyperus rotundus, were effectively protected without any infestation for up to 6 months. Kim et al, 2003 reported the insecticidal activities of aromatic plant extracts and essential oils against Sitophilus oryzae and Callosobruchus chineensis.…”
Section: Resultsmentioning
confidence: 99%
“…The treated and infested beans were incubated at 24, 48, 72 and 96 hours and the mortality rate of the insects as a result of effect of the extract after treatment as reported by Raja et al [9]. The effect of the extract was studied for two weeks to determine the efficacy on the oviposition of the insects.…”
Section: Culturing and Maintenance Of The Insectsmentioning
confidence: 99%